PENANAMAN NILAI-NILAI KARAKTER DI SEKOLAH ALAM PALEMBANG - Miftha Indasari (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
This study aims to describe the planning, implementation, and assessment of character education at the Palembang School of Nature. The research methodology used in this research is qualitative-descriptive research where data collection is done through observation, interview, and documentation. The results obtained are: a) character education planning conducted by principals and teachers every year. The highly emphasized character values are religious characters; b) Implementation of character education is done by integrating character values through teaching and extracurricular activities; c) Character education assessments are conducted by classroom teachers and seen in the application of the student's character values when students are at school and the presence of an assessment indicator that will be an evaluation for teachers and principals to give to parents. The conclusion that the planning, execution, and assessment of character education at Palembang Natural School is good. Suggestions that researchers can further examine the imposition of character values in other schools.